Application of modern computational methods in modeling bridge abutments: capabilities of the Lira-SAPR software tool (Международный научный журнал «Инженер», 2026)
This article considers the application of the finite element method in modeling bridge supports, taking intoaccount various types of loads - static, dynamic and temperature effects. To achieve this goal, the Lira-CADsoftware package was selected, which allows analyzing structures with a full reflection of their geometry,along with their physical and mechanical properties. This system provides extensive opportunities foraccurately determining load parameters, taking into account seismic and other external influences. The finiteelement approach simplifies the calculation process by dividing structures with complex geometry intosimpler elements, which increases the accuracy of engineering analysis and plays an important role inensuring the reliability and service life of structures.